Simonas Daukantas’s Narrative – The Foundation for Lithuanian Identity - Kuolys, Darius (Senoji Lietuvos literatūra, 2019)
In this article, the author analyses the images, vocabulary, and ideas of Simonas Daukantas’s historical narrative and discusses the programme for reviving the Lithuanian nation that is laid out in this narrative. In Daukantas’s programme, freedom and language come up as the key components of the Lithuanian identity and the establishment of native language in public life and taking back freedom as the main imperatives. The article also addresses the way in which Simonas Daukantas’s narrative further influenced the development of Lithuanian culture and the impetus that the union of freedom, language and land declared by Daukantas gave to the modern Republic of Lithuania.
Keywords: Simonas Daukantas; historical narrative; freedom; Lithuanian language; Lithuanian nation; Republic of Lithuania